A measure of well-being efficiency based on the World Happiness Report - Francesco Sarracino; Kelsey J. O'Connor (Global Labor Organization (GLO), 2022)
We propose a measure of well-being efficiency to assess countries' ability to transform inputs into subjective well-being (Cantril ladder). We use the six inputs (real GDP per capita, healthy life expectancy, social support, freedom of choice, absence of corruption, and generosity) identified in the World Happiness Reports and apply Data Envelopment Analysis to a sample of 126 countries. Efficiency scores reveal that high ranking subjective well-being countries, such as the Nordics, are not strictly the most efficient ones. Also, the scores are uncorrelated with economic efficiency. This means that the implicit assumption that economic efficiency promotes well-being is not supported. Well-being efficiency can be improved by changing the amount (scale) or composition of inputs and their use (technical efficiency). For instance countries with lower unemployment, and greater healthy life expectancy and optimism are more efficient.
Keywords: I31; E23; D60; O47; O15; 330; subjective well-being; World Happiness Report; efficiency; Data Envelopment Analysis